Trade and Employment : Stylized Facts and Research Findings - Hoekman, Bernard; Winters, L. Alan (World Bank, Washington, DC, 2012)
The substantial literature investigating the links between trade, trade policy, and labor market outcomes-both returns to labor and employment-has generated a number of stylized facts, but many open questions remain. This paper surveys the subset of the literature focusing on trade policy and integration into the world economy. Although in the longer run trade opportunities can have a major impact in creating more productive and higher paying jobs, this literature tends to take employment as given. A common finding is that much of the shorter run impacts of trade and reforms involve reallocation of labor or wage impacts within sectors. This reflects a pattern of expansion of more productive firms-especially export-oriented or suppliers to exporters-and contraction and adjustment of less productive enterprises in sectors that become subject to greater import competition. Wage responses to trade and trade reforms are generally greater than employment impacts, but trade can only explain a small fraction of the general increase in wage inequality observed in both industrial and developing countries in recent decades. A feature of the literature survey is that the focus is almost exclusively on industries producing goods. Given the importance of service industries as a source of employment and determinants of competitiveness, the paper argues that one priority area for future research is to study the employment effects of services trade and investment reforms.